Comparing Irrigation Systems and Strategies for Table Grapes in the Weathered Granite-gneiss Soils of the Lower Orange River Region - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2016)
Drip and micro-sprinkler irrigation systems were compared in a Thompson Seedless/Ramsey table grape vineyard in a weathered granite-gneiss soil in the Lower Orange River region. For each system, two different irrigation strategies were investigated. Drip irrigation frequencies of two days or longer, induced more water constraints in grapevines compared to micro-sprinkler irrigation applied at the same frequencies in the 1996/97 and 1997/98 seasons. Higher water constraints imposed by drip irrigation had negative effects on vegetative growth, berry size and grape quality compared to micro-sprinkler irrigation. However, responses of drip irrigated grapevines were comparable to micro-sprinkler irrigated grapevines when drip irrigations were applied daily in the 1998/99 and 1999/2000 seasons. Daily, early morning drip irrigation increased evapotranspiration (ET) by 6% compared to drip during the warmest part of the day. Drip irrigation suppressed weed growth considerably compared to micro-sprinklers. Daily ET of the drip irrigated grapevines was substantially lower compared to micro-sprinkler irrigated grapevines that received either two or three irrigations per week. In the case of micro-sprinklers, the higher frequency increased ET by 8% compared to the lower irrigation frequency. Since micro-sprinkler irrigation invariably produced higher yields than drip irrigation during the four seasons, it should be the preferred system for irrigation of table grapes under the given atmospheric and soil conditions. If water resources are limited, or if high water cost reduces table grape profitability, drip irrigation merits consideration as an alternative. However, daily drip irrigation will be required during the growing season to maintain acceptable yields and grape quality.